Aktualisasi Patrap Triloka Ki Hadjar Dewantara pada Organisasi IPNU-IPPNU Kecamatan Ngancar Kabupatenkediri (2021-2023) - Krisna Putra Aji Purnama; Arik Cahyani; Minto Santoso (International Forum of Researchers and Lecturers, 2026)
This research is motivated by how the IPNU-IPPNU organization in Ngancar sub- district actualizes the Patrap Triloka concept initiated by Ki Hadjar Dewantara. Where the purpose of this study is to determine the actualization of the thoughts or values of Patrap Triloka Ki Hadjar Dewantara in IPNU-IPPNU Ngancar sub-district for the 2021-2023 period. This study uses a qualitative research method with data description in the form of written word descriptions The data collection method in this study uses documentation and in-depth interviews with the daily management of the IPNU-IPPNU organization in Ngancar sub-district. The results shown in this study indicate that in running the organization, the leadership carried out by the IPNU-IPPNU management of Ngancar District for the 2021-2023 period has implemented the values contained in Patrap Triloka, namely Ing Ngarso sung Tulodho, Ing madyo Mangun Karso and Tut Wuri Handayani which were initiated by KI Hadjar Dewantara. This study concludes that the IPNU-IPPNU Organization has a high relevance in efforts to instill values in Patrap Tiloka which were initiated by KI Hadjar Dewantara in an effort to improve the quality of youth at the level of male and female students of Nahdlatul Ulama in Ngancar District.